Characterization of alkali-activated chrysopogon zizanioides natural fibers as reinforcement for energy-efficient biocomposite applications - Nasmi Herlina Sari; Sujita Sujita; Edi Syafri; Suteja Suteja (Mechanical Engineering for Society and Industry, 2025)
This study examines the characteristics of alkali-activated Chrysopogon zizanioides natural fibers (CZFs) to determine their applicability as reinforcements in energy-efficient biocomposite applications. Unlike earlier research, which has mostly focused on conventional natural fibers, this paper proposes CZFs as a fresh, sustainable reinforcing possibility. The study investigates the impact of different levels of NaOH (1%, 3%, and 5%) on fiber structure and functionality, offering new insights into optimizing alkali activation for improved interfacial bonding and strength in biocomposites. The results show that alkaline treatment significantly influenced the structural and functional properties of the fibers. X-ray diffraction (XRD) analysis revealed an increase in crystallinity index from 36.17% in untreated fibers to 65.74% in those treated with 5% NaOH, indicating significant removal of amorphous components. FTIR spectra confirmed the reduction of non-cellulosic functional groups, while TGA/DTA analysis demonstrated improved thermal resistance, with a maximum char residue of 4.46% at 600 °C. Mechanical tests showed tensile strength increased from 252 ± 25 MPa to 553 ± 26 MPa and elongation from 4.1% to 5.8%, while SEM analysis revealed cleaner, rougher surfaces that promote fiber–matrix bonding. Additionally, fiber density rose from from 410 ± 20 to 980 ± 20 Kg/m³, and moisture content declined from 8.9% to 5.3%, reflecting improved dimensional stability. Among all treatments, the 5% NaOH-treated fibers offered the most optimal combination of structural, thermal, and interfacial performance. These results indicate that alkali-modified CZFs are promising candidates for use in energy-efficient biocomposites, particularly for lightweight structural components, automotive panels, and sustainable packaging requiring thermal durability and high stiffness.